2014
DOI: 10.3171/2014.4.jns121952
|View full text |Cite
|
Sign up to set email alerts
|

A novel, reproducible, and objective method for volumetric magnetic resonance imaging assessment of enhancing glioblastoma

Abstract: Objective Robust methodology that allows objective, automated, and observer-independent measurements of brain tumor volume, especially postresection, is lacking; hence, determination of tumor response and progression in neuro-oncology is unreliable. Our objective was to determine if a semi-automated, volumetric method for quantifying enhancing tissue would perform with high reproducibility and low interobserver variability. Methods Fifty-seven scans from 13 patients with glioblastoma (GBM) were assessed, usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 24 publications
4
27
0
Order By: Relevance
“…Such advances include visual tracing of the tumor perimeter (planimetry method) 7,8 ; computer-assisted, threshold-based methods 8,9 ; and fully automated, computer facilitated methods. [10][11][12] Since the original Macdonald criteria were developed, new criteria have been proposed to assess therapeutic responses in both human and veterinary neuro-oncology pa-…”
Section: Conclusion and Clinical Relevancementioning
confidence: 99%
“…Such advances include visual tracing of the tumor perimeter (planimetry method) 7,8 ; computer-assisted, threshold-based methods 8,9 ; and fully automated, computer facilitated methods. [10][11][12] Since the original Macdonald criteria were developed, new criteria have been proposed to assess therapeutic responses in both human and veterinary neuro-oncology pa-…”
Section: Conclusion and Clinical Relevancementioning
confidence: 99%
“…For high grade gliomas the Response Assessment in Neuro‐Oncology criteria also subjectively takes into account the T2 or FLAIR area in assessing response. Volumetric assessment methods are yet to be standardized and include using varying software packages …”
Section: Guidelines On Implementation Of Standardized Magnetic Resonamentioning
confidence: 99%
“…Tumor volumes were calculated through semi-automated volumetric analysis using Brainlab software (Brainlab, iPlanNet version 2.3.1.215.1, Munich, Germany) by three observers (a neurosurgeon, a radiologist, and a trained medical student). Previous literature stated the use of this method to be reliable for tumor measurements [4,5]. All observers are skilled in interpreting MR images for brain tumors.…”
Section: Test Methodsmentioning
confidence: 99%
“…Using volumetric analysis, it is possible to quantify the EOR using MR imaging. Prior studies using semi-automated methods for this purpose found a high interobserver agreement [4,5]. However, when manual segmentation is used, a low interobserver agreement in the assessment of tumor resection rates on magnetic resonance imaging (MRI) is described.…”
Section: Introductionmentioning
confidence: 99%